2003
DOI: 10.5271/sjweh.746
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues in evaluating workplace interventions to reduce work-related musculoskeletal disorders through mechanical exposure reduction

Abstract: Researchers of work-related musculoskeletal disorders are increasingly asked about the evidentiary base for mechanical exposure reductions. Mixed messages can arise from the different disciplinary cultures of evidence, and these mixed messages make different sets of findings incommensurate. Interventions also operate at different levels within workplaces and result in different intensities of mechanical exposure reduction. Heterogeneity in reporting intervention processes and in measuring relevant outcomes mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…For example, it has been found that different stakeholders have conflicting mental models about what constitutes success (Cole et al, 2003;Shannon & Cole, 2004). Detecting these different perspectives may help to explain how different motivations drive differences in key stakeholders' behaviours during the intervention process.…”
Section: Mental Modelsmentioning
confidence: 99%
“…For example, it has been found that different stakeholders have conflicting mental models about what constitutes success (Cole et al, 2003;Shannon & Cole, 2004). Detecting these different perspectives may help to explain how different motivations drive differences in key stakeholders' behaviours during the intervention process.…”
Section: Mental Modelsmentioning
confidence: 99%
“…While ergonomics interventions are usually aimed to reduce the risk of MSD, intervention effects on biomechanical exposure are often used as proxies of health effects, assuming that exposure is predictive of risk (Westgaard and Winkel, 1997;Lö tters and Burdorf, 2002;Cole et al, 2003). One major reason is that the exposure effects of an intervention have a much shorter latency (if any) than health outcomes, making them more readily accessible, in particular to practitioners.…”
Section: Job Exposure Assessment For Interventionsmentioning
confidence: 98%
“…Westgaard and Winkel, 1997;Silverstein and Clark, 2004;van der Molen et al, 2005;Brewer et al, 2006;Boocock et al, 2007;Denis et al, 2008). While the ultimate goal of the intervention is to reduce the risk of contracting or maintaining WMSD, changes in biomechanical exposure accompanying the intervention are often used as a proxy for its eventual effect on health (Westgaard and Winkel, 1997;Lö tters and Burdorf, 2002;Cole et al, 2003). Due to constraints on time and resources, safety and ergonomics practitioners are particularly compelled to judging intervention effects by how they affect exposure.…”
Section: Introductionmentioning
confidence: 97%
“…We live in an age of evidence-based practice in the healthcare sector; yet, as pointed out by Shamian and El-Jardali, despite the sheer volume of these reports, there has been very little high-quality research evidence available upon which to base effective interventions. But the scope of the challenges faced when conducting rigorous workplace intervention research should not be underestimated (Cole et al 2003).…”
Section: From the National Survey On The Work And Health Of Nursesmentioning
confidence: 99%